Pengembangan Pengembangan Kambing Peranakan Etawah Pada Bumdes Pujiku Artomoro Desa Terjun Gajah Kecamatan Berata Kabupaten Tanjung Jabung Barat - Adriani, Adriani; Mairizal, Mairizal; Elyanti, Elyanti; Yurleni, Yurleni; Ramadlan, Ahmad; Yusuf, M.; Winandha, Cut Sheilla Saomyra (Jurnal Pengabdian Masyarakat Pinang Masak, 2024)
The aim of this activity is to develop Etawah crossbreed goats (PE) in Pujiku Artomoro Bumdes, Terjun Gajah Village, Betara District. This activity is a collaboration between PUI PT Sifas Jambi University and PetroChina International Jabung Ltd in community empowerment.The main target of this activity is Bumdes Pujiku Artomoro. Activities carried out include counseling, training, building goat pens, helping goats, and developing forage. At the end of the activity, monitoring and evaluation are carried out. This empowerment activity was attended by 25 people from Bumdes Pujiko Artomoro. Counseling and practical activities were carried out for 2 days with resource persons from the Jambi University PUI team, the Plantation and Livestock Service, and PetroChina International Jabung Ltd. The construction of the goat pen was carried out in one of the Bumdes members' houses, with an area of 72 m2. To provide forage, 4000 elephant grass seeds were planted. To accelerate the development of goat livestock, 35 goats (32 females and 3 males) are provided. The results of monitoring and evaluating activities show that Bumdes members have a good perception of the activities carried out and are in line with the direction of Bumdes development. The conclusion from this activity is that the empowerment is going according to plan, and Bumdes members have implemented the goat-raising system well.